Total Neighborhood Magic Labeling: A New Variant of Magic Labeling - N P Shrimali, Y M Parmar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, we introduce a total neighborhood magic labeling, which is a variant of magic labeling. A total neighborhood magic labeling on a graph with